Home to Chicory Lane : a Chicory Inn Novel - Raney, Deborah (Thorndike, Maine : Center Point Large Print, 2015)
"Now that their kids are grown, Audrey and Grant Whitman have converted their home into a cozy bed-and-breakfast. But then their youngest daughter shows up during opening weekend with a loaded U-Haul--and no husband. Now they'll have to figure out how to help the young couple in addition to running a new inn"--
Keywords: Bed and breakfast accommodations -- Fiction; Large type books; Domestic fiction; Christian fiction